(untitled) (KULT_online, 2015)
In the coursebook Mehrsprachigkeitstheorie, Jörg Roche summarizes the most important results of research on multilingualism and considers cognitive and cultural aspects of language acquisition and language management. Roche discusses different studies on multiple language acquisition as well as language processing and relates them to didactic concepts and methods for teaching culture. Furthermore, he examines a wide range of cognitive, social, and educational factors influencing the acquisition and development of multilingualism and offers first insights into their relevance for the practice of multilingual teaching.